MIRERC 043/2025: PATTERNS, RISK FACTORS AND TREATMENT OUTCOMES OF DRUG-RESISTANT TUBERCULOSIS IN MERU COUNTY. - Onchari, Dr. Divina; Dr. Joyster Mungania (MUST Institutional Research Ethics Review Committee (MIRERC), 2025)
Background: Tuberculosis (TB) infection is a significant global public health threat and one of the leading causes of mortality from an infectious disease. The emergence of drug-resistant forms of tuberculosis complicates efforts to control the disease, as these strains are more difficult to treat, leading to prolonged illness, increased healthcare costs, and higher mortality rates. Different types of resistance have been documented globally, but these and contributors to DR TB in Meru County are not well established. This study aims to document resistance rates and factors that could contribute to resistance, which can then be targeted for modification whenever feasible. Objectives: To describe the resistance patterns to DR TB, determine risk factors associated with drug resistance, and document subsequent treatment outcomes in patients with DR TB in Meru County. Study site: All eleven sub-counties of Meru County. Methodology: This retrospective study will collect data on patients with bacteriologically confirmed TB from the TIBU platform from January 2021 to December 2024. Demographics, clinical characteristics, and treatment outcomes will be summarized in frequencies and proportions. Factors associated with DR TB will be determined through Pearson’s chi-square test at the bivariate level and subjected to multivariate logistic regression to identify independent association. A P level of less than 0.05 will be considered significant. Expected outcomes: Understanding the risk factors contributing to drug-resistant TB can guide targeted prevention efforts and inform public health strategies to mitigate these risks. Insights into treatment outcomes, including success, failure, mortality, relapse rates, and adverse effects, will help refine existing treatment protocols.